2016
DOI: 10.5966/sctm.2015-0243
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Impact Th17 and Th1 Responses Through a Prostaglandin E2 and Myeloid-Dependent Mechanism

Abstract: A novel prostaglandin E2-dependent and myeloid cell-mediated mechanism by which human mesenchymal stem cells (MSCs) can reciprocally induce human Th17 while suppressing Th1 responses has implications for the use of, as well as monitoring of, MSCs as a potential therapeutic for patients with multiple sclerosis and other immune-mediated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
52
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 52 publications
5
52
0
Order By: Relevance
“…Haribhai et al showed that TGF-b-producing M2a macrophages differentiated Th17 cells into anti-inflammatory iTreg cells (Haribhai et al, 2016). For MSCs and Th17 interactions, Qu et al reported that Th17 cells were suppressed by IL-10 secreted by MSCs (Qu et al, 2012), Rozenberg et al showed that PGE2 secreted from MSCs increased the Th17 response but suppressed the Th1 response (Rozenberg et al, 2016), and Ghannam et al noted that MSCs increased Treg cells by suppressing Th17 cells (Ghannam et al, 2010). Our findings revealed that the Th17 frequencies of the A-PBMC group was significantly higher than those of the remaining groups, except M1 and M2c.…”
Section: Discussionsupporting
confidence: 47%
“…Haribhai et al showed that TGF-b-producing M2a macrophages differentiated Th17 cells into anti-inflammatory iTreg cells (Haribhai et al, 2016). For MSCs and Th17 interactions, Qu et al reported that Th17 cells were suppressed by IL-10 secreted by MSCs (Qu et al, 2012), Rozenberg et al showed that PGE2 secreted from MSCs increased the Th17 response but suppressed the Th1 response (Rozenberg et al, 2016), and Ghannam et al noted that MSCs increased Treg cells by suppressing Th17 cells (Ghannam et al, 2010). Our findings revealed that the Th17 frequencies of the A-PBMC group was significantly higher than those of the remaining groups, except M1 and M2c.…”
Section: Discussionsupporting
confidence: 47%
“…Another example of reciprocal regulation was seen with prostaglandin E2 (PGE 2 ), a proinflammatory chemical that signals through a G‐protein‐coupled receptor. PBMCs treated with PGE 2 produced more IL‐17A and less IFNγ . Reciprocal regulation also occurred when Th17 cells were cultured with mesenchymal stem cells that produced and secreted PGE 2 .…”
Section: Discussionmentioning
confidence: 90%
“…PBMCs treated with PGE 2 produced more IL‐17A and less IFNγ . Reciprocal regulation also occurred when Th17 cells were cultured with mesenchymal stem cells that produced and secreted PGE 2 . Thus, agents that cause G protein signaling and elevate cAMP tend to promote IL‐17A responses while inhibiting IFNγ.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the clinical applications of allogeneic mesenchymal stem cells include organ transplantation and the treatment of multiple sclerosis, graft versus host disease and Crohn's disease 30 . Interestingly, mediation of the regulatory effect of mesenchymal stem cells on Th1 and Th17 responses by CD14 + myeloid cells and the production of PGE 2 was recently reported 31 . Confirmation of the reduced allogenicity of MDSCs in appropriate in vivo models would open the door to the therapeutic use of ex vivo ‐ or in vivo ‐generated allogeneic or third‐party MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…30 Interestingly, mediation of the regulatory effect of mesenchymal stem cells on Th1 and Th17 responses by CD14 + myeloid cells and the production of PGE 2 was recently reported. 31 Confirmation of the reduced allogenicity of MDSCs in appropriate in vivo models would open the door to the therapeutic use of ex vivoor in vivo-generated allogeneic or third-party MDSCs. In general, the pattern of cytokines secreted in cocultures of MDSCs and allogeneic PBMCs was consistent with the immunomodulatory activity of these cells.…”
Section: Discussionmentioning
confidence: 99%